A Forkhead box G1 (FOXG1) gene mutation in an Indian patient with a congenital variant of Rett syndrome. - Dr. Sai Chandar Dudipala; Dr. Naveen Reddy Cheruku; Dr. Krishna Chaithanya Battu (Pediatric Review: International Journal of Pediatric Research, 2020)
A congenital variant of rett syndrome or Forkhead box G1 (FOXG1) syndrome is a rare neurodevelopmental disorder characterized by global developmental delay, microcephaly, autistic features, early-onset dyskinesia, and seizures. Once it was described as one atypical variant of rett syndrome but now considered as a separate entity. The current study found one girl carrying the de novo c.500-501incG frameshift mutation in the FOXG1 gene by genetic analysis during the evaluation for severe chronic encephalopathy. In literature, only one case was reported from India with FOXG1 mutation. The FOXG1 mutation should be considered in children with a history of global developmental delay, dyskinesia, and microcephaly with characteristic brain neuroimaging findings.